Humoral and cellular immunity to hepatitis B virus-derived antigens: comparative activity of Freund complete adjuvant alum, and liposomes. - Sanchez, Y (1980)
Complete Freud adjuvant, aluminum gel, and liposomes were compared for their ability to enhance the immunogenicity of an intact 22-nm HBsAg particle vaccine and an HBsAg-derived polypeptide vaccine in guinea pigs. Both humoral and cell-mediated immune responses were evaluated. The greatest immune response was obtained with complete Freund adjuvant, regardless of the antigen preparation. Aluminum gel appeared to be a better adjuvant for 22-nm HBsAg particles, but the liposomes rendered polypeptide preparations more immunogenic. The possibility that various proportions were entrapped in aqueous compartments instead of being inserted into the lipid bilayers of liposomes might account for this difference. The development of both humoral and cellular immunity was dependent upon the use of an adjuvant, because aqueous preparations had poor immunogenicity.